2013
DOI: 10.1002/dvdy.23968
|View full text |Cite
|
Sign up to set email alerts
|

On the role of intrinsic and extrinsic forces in early cardiac S‐looping

Abstract: Background Looping is a crucial phase during heart development when the initially straight heart tube is transformed into a shape that more closely resembles the mature heart. Although the genetic and biochemical pathways of cardiac looping are well-studied, the biophysical mechanisms that actually effect the looping process remain poorly understood. Using a combined experimental (chick embryo) and computational (finite element modeling) approach, we study the forces driving early s-looping when the primitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 51 publications
(135 reference statements)
2
34
0
Order By: Relevance
“…More recently, Shyer et al revealed the role of mechanical stresses in the formation of villi in the gut [8]. Forces extrinsic to the primitive heart tube also are important players during cardiac looping [14,26,40,41]. Results from these studies suggest that the SPL plays a mechanical role in facilitating cardiac torsion that may be similar to the role of the VM in inducing brain torsion reported here.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…More recently, Shyer et al revealed the role of mechanical stresses in the formation of villi in the gut [8]. Forces extrinsic to the primitive heart tube also are important players during cardiac looping [14,26,40,41]. Results from these studies suggest that the SPL plays a mechanical role in facilitating cardiac torsion that may be similar to the role of the VM in inducing brain torsion reported here.…”
Section: Discussionsupporting
confidence: 66%
“…In a sense, this process can be considered as a transfer of chirality or L -R asymmetry, from the heart to the brain tube through mechanics. Following the first phase of cardiac looping (c-looping), brain torsion in turn ensures the normal helical looping of the heart during the subsequent s-looping [41]. This type of transfer of chirality between two co-developing organs at the same length scale has not previously been examined in detail, although the transfer of chirality from microscopic-to-macroscopic scale in plant tendrils has recently been studied [34].…”
Section: Discussionmentioning
confidence: 99%
“…The forces that drive s-looping apparently are exerted by external loads, including those supplied by the brain tube as it bends [31]. …”
Section: Cardiac Morphogenesismentioning
confidence: 99%
“…It has been found, however, that this “ in vitro looping ” is simpler than the normal “ in situ looping ” since it produces heart loops that are bend only in a single plane (planar looping) but lack a helical shape (spatial looping) (Flynn et al, 1991; Latacha et al, 2005; Rémond et al, 2006; Ramasubramanian et al, 2013). Contemporary hypotheses of cardiac looping mechanics, therefore, attribute the bending of the tubular embryonic heart primarily to forces intrinsic to its myocardial wall (Latacha et al, 2005; Taber, 2006; Taber et al, 2010) while its deformation into helical shapes is attributed primarily to factors outside of the heart (Taber, 2006; Taber et al, 2010; Männer, 2013).…”
Section: Introductionmentioning
confidence: 99%